Optimization of the methodology for assessing the specific endurance of football players - Lavrichenko, V. V.; Kalinina, I. N.; Grigoryan, M. R.; Deb, M. M. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the physiological focus of the modified J. Bangsbo football sprint test, where the reliability of data on the development of anaerobic and aerobic energy supply mechanisms ensures the validity and reliability of the assessment of the special endurance of football players.